The Earlier, the Better. Global and Indonesian Views on TEYL (Teaching English to Young Learners) - Amin, Muhammad; Tsaqiila, Thalia Qaulan; Zamzam, Ahmad; Arfah, Hajriana (Universitas Hamzanwadi, 2023)
Teaching English to young learners (TEYL) has been attracting the attention of governments (as policymakers), TEYL practitioners, and students' parents alike. For some, among various issues surrounding TEYL, issues regarding the role of students' first language (L1), language skills to focus on, and when to start to teach English are among the critical issues in TEYL. This qualitative study assesses how academics have measured and conceived teaching English to young learners across 17 empirical studies from global and Indonesian contexts. Its specific goal is to determine what can be drawn from these investigations and what critical issues remain. Results indicate that English to young learners from the global context is divided into two opposing parties (i.e., proponents and opponents of early start). Meanwhile, Indonesian EYL practitioners (i.e., researchers, teachers, schools) and stakeholders (i.e., parents) mostly favor the early start. Yet, current research findings serve to deepen and broaden theoretical understandings of The TEYL and their impact in the particular situation of teaching English to young learners. Future research and practical implications are discussed.